2015
DOI: 10.1111/nan.12260
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein response is activated in Lewy body dementias

Abstract: Overall, these results give emphasis to the role of UPR in Lewy body dementias, and suggest that Lewy body degeneration, in combination with AD-type pathologies, is associated with increased UPR activation to a greater extent than AD alone, possibly as a consequence of the increasing load of ER proteins. This work also highlights a novel opportunity to explore the UPR as a therapeutic target in synuclein diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 48 publications
(64 reference statements)
2
35
0
1
Order By: Relevance
“…The roles of these as well as other potentially relevant mechanisms for cognitive impairment, such as the unfolded protein response 51 , the ubiquitin–proteasome system 52 , and increased neurogenesis (for example, in response to neurotrophic factors) 53 , need to be explored further (see Management section below).…”
Section: Mechanismsmentioning
confidence: 99%
“…The roles of these as well as other potentially relevant mechanisms for cognitive impairment, such as the unfolded protein response 51 , the ubiquitin–proteasome system 52 , and increased neurogenesis (for example, in response to neurotrophic factors) 53 , need to be explored further (see Management section below).…”
Section: Mechanismsmentioning
confidence: 99%
“…In Parkinson’s disease, elevated expression of BiP and other UPR proteins have been reported in many cellular and animal models of Parkinson’s disease (Baek et al, 2016). Interestingly, the SH-SY5Y cell model exhibited lower BiP mRNA levels when treated with the neurotoxin 1-methyl-4-phenylpyridinium (MPP+); however, treating the same cell model with 6-hydroxydopamine, another Parkinson’s disease inducer, raised BiP mRNA levels.…”
Section: Clinical Significancementioning
confidence: 99%
“…Additional molecular alterations converge in the pathogenesis of DLB, including impaired autophagy and ubiquitin-proteasome system of protein (4650), as well as altered responses to protein misfolding (51). Preliminary studies have shown impaired mitochondrial activity and oxidative damage involving proteins, lipids, and DNA in the neocortex in DLB (52, 53); α-synuclein is one of the targets of oxidative damage in the frontal cortex in DLB (54).…”
Section: Introductionmentioning
confidence: 99%